The hoof-printed rock - Maahlamela, David wa (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2014)
Many of these poems, although written in English, are inspired by Sepedi idioms and proverbs. Some invoke township and village life, others the observations and questions that come from writing poetry and experiences of travelling to different countries to read my poems. Others dwell on the political transformation in South Africa, or its absence, and on my own spiritual transformation.
Keywords: South African poetry (English) -- 21st century